Two new species of the bathyal holothurian genus Pannychia (Elasipodida, Laetmogonidae) from Japanese waters - Ogawa, Akito; Kobayashi, Itaru; Kohtsuka, Hisanori; Fujita, Toshihiko (Zootaxa, 2023)
Sea cucumbers are one of the most common large animals in the deep-sea benthic communities, and those of the genus Pannychia are particularly abundant in the bathyal North Pacific Ocean. In Japanese waters, three species of Pannychia have been reported, mainly from the northern and eastern parts of the country. Here, we describe two new species from the western part of Japan. These two new species were placed in Pannychia by the presence of dorsal papillae on the ventrolateral radii and the presence of large wheel ossicles with rim teeth. They are distinguished from all other nominal species of Pannychia on the basis of the morphological characteristics of their body wheel ossicles. Pannychia nagasakimaruae sp. nov. has a unique ossicle composition in its dorsal and ventral body walls: four forms of wheel ossicles. Pannychia rinkaimaruae sp. nov. differs from other congeners in its small wheel ossicles in the dorsal and ventral body walls, which have conical rim teeth. We barcoded partial COI gene sequences from holotypes and paratypes of two new Japanese species. Our molecular phylogenetic analysis showed that these two new morphologically recognized Japanese species form distinct clades separated from other Pacific Pannychia species, so that the two new Japanese species were also supported by genetic results. In addition, we describe and visualize the poorly calcified calcareous rings of the two new species using X-ray μCT system, a useful method for observing such structures, which are important structures in holothurian anatomy.